Bombesin Preserves Goblet Cell Resistin-Like Molecule β During Parenteral Nutrition but Not Other Goblet Cell Products. (September 2016) - Busch, Rebecca A.; Heneghan, Aaron F.; Pierre, Joseph F.; Neuman, Joshua C.; Reimer, Claire A.; Wang, Xinying; Kimple, Michelle E.; Kudsk, Kenneth A.
Introduction: Parenteral nutrition (PN) increases the risk of infection in critically ill patients and is associated with defects in gastrointestinal innate immunity. Goblet cells produce mucosal defense compounds, including mucin (principally MUC2), trefoil factor 3 (TFF3), and resistin-like molecule β (RELMβ). Bombesin (BBS), a gastrin-releasing peptide analogue, experimentally reverses PN-induced defects in Paneth cell innate immunity. We hypothesized that PN reduces goblet cell product expression and PN+BBS would reverse these PN-induced defects. Methods : Two days after intravenous cannulation, male Institute of Cancer Research mice were randomized to chow (n = 15), PN (n = 13), or PN+BBS (15 µg tid) (n = 12) diets for 5 days. Defined segments of ileum and luminal fluid were analyzed for MUC2, TFF3, and RELMβ by quantitative reverse transcriptase polymerase chain reaction and Western blot. Th2 cytokines interleukin (IL)–4 and IL-13 were measured by enzyme-linked immunosorbent assay. Results : Compared with chow, PN significantly reduced MUC2 in ileum ( P < .01) and luminal fluid ( P = .01). BBS supplementation did not improve ileal or luminal MUC2 compared with PN ( P > .3). Compared with chow, PN significantly reduced TFF3 in ileum ( P < .02) and luminal fluid ( P < .01). BBS addition did not improve ileal or luminal TFF3 compared with PN ( P > .3). Compared with chow, PN significantly reduced ileal RELMβ ( P < .01). BBS supplementation significantly increased ileal RELMβ to levels similar to chow ( P < .03 vs PN; P > .6 vs chow). Th2 cytokines were decreased with PN and returned to chow levels with BBS. Conclusion : PN significantly impairs the goblet cell component of innate mucosal immunity. BBS only preserves goblet cell RELMβ during PN but not other goblet cell products measured.